Network Connectivity Quality Assessment Case of Major Roads of Padangsidimpuan City - Fithriyah Patriotika; Hitapriya Suprayitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Institut Teknologi Sepuluh Nopember, 2018)
Assessment of network connectivity in this study was done by using a special matrix operation. The quality of connectivity is measured based on network performance comparison value, between those of existing road network against those of expected road network. This network connectivity quality is derived into three aspects: number of connected nodes, total shortest path distance and total road length. The quality of the road network connectivity for the Truck Class 1 can be concluded as follows: The connectivity quality of the existing road network, in order to be equals to the expected road network needs an addition of 2 nodes: freight terminal 1 and freight terminal 2 and needs an addition of 1 ringroad and 2 access road, while warehouse in the existing road network must be abolished. The difference of total roads length between the existing network compared to the expected road network is 12.77 km, equal to a ratio of 0.76. Therefore, the existing road network requires an addition of 12.77 km in order to achieve the same quality as the expected road network. The total shortest path distance of the existing road network is infinite (∞) and the one of expected road network is 295.44 km.